Merdeka Mengajar Platform: A Digital Innovation in Education - Makkiyah, Fawaidul; Rohmatulloh, Ulul Azmi Nur; Setyowati, Sri; Khamidi, Amrozi (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2025)
Digital transformation in education brings opportunities and challenges for educators in Indonesia, especially in integrating technology into learning practices. As an innovative step, the Merdeka Mengajar Platform (PMM) is here to improve teacher competence and support the implementation of the Merdeka Curriculum. This study examines the use of PMM at UPT SDN 144 Gresik, especially in helping teachers prepare interactive and student-centered learning plans. Using a qualitative approach with descriptive methods, data was obtained through interviews, observations, and document analysis. The results of the study indicate that PMM is effective in improving the quality of teaching and professional competence of teachers, despite obstacles such as limited infrastructure, outdated devices, slow internet connections, and difficulties in adapting to digital technology for senior teachers. This study provides practical insights into strategies to overcome these obstacles, such as improving infrastructure, more targeted training, and developing offline features to support areas with limited internet access. With these findings, PMM shows its potential in driving a more innovative and inclusive educational transformation, in line with the vision of improving the quality of education in Indonesia.